Pelatihan Tari Padduppa Pada Siswa SMPN SATAP 6 Ponre - sandi sandi sandi; sriwahyuni uni; Rini Reski Putri Damayanti Rini; Nurfadillah Nur; marsani utami (Jurnal Abdimasa Pengabdian Masyarakat, 2022)
Padduppa dance is one of the local bugis-Makassarase wisdom that is often performed to welcome guests. Padduppa dance was originally used for special entertainment for kings and dignitaries only at weddings. But over time this dance can be performed at any evennt, whether welcoming guests, circumcisions, weddings and other activities. Thus, students of KKN-DIK (Educational Work Course) University of Muhammadiyah Bone, Mattampae Village, took the initiative to hold Padduppada Dance training for students of SMPN SATAP 6 Ponre. This training aims to add insight and skills for the next generation who should be the inheritors of the culture in their area. Student who are trained already have basic skills in the world of dance so the Padduppa dance training process is not so difficult.